Differential regulation of KCa2.1 (KCNN1) K+ channel expression by histone deacetylases in atrial fibrillation with concomitant heart failure. Issue 11 (10th June 2021) - Rahm, Ann‐Kathrin; Wieder, Teresa; Gramlich, Dominik; Müller, Mara Elena; Wunsch, Maximilian N.; El Tahry, Fadwa A.; Heimberger, Tanja; Sandke, Steffi; Weis, Tanja; Most, Patrick; Katus, Hugo A.; Thomas, Dierk; et al.
Abstract: Atrial fibrillation (AF) with concomitant heart failure (HF) poses a significant therapeutic challenge. Mechanism‐based approaches may optimize AF therapy. Small‐conductance, calcium‐activated K + (KCa, KCNN ) channels contribute to cardiac action potential repolarization. KCNN1 exhibits predominant atrial expression and is downregulated in chronic AF patients with preserved cardiac function. Epigenetic regulation is suggested by AF suppression following histone deacetylase (HDAC) inhibition. We hypothesized that HDAC‐dependent KCNN1 remodeling contributes to arrhythmogenesis in AF complicated by HF. The aim of this study was to assess KCNN1 and HDAC1–7 and 9 transcript levels in AF/HF patients and in a pig model of atrial tachypacing‐induced AF with reduced left ventricular function. In HL‐1 atrial myocytes, tachypacing and anti‐ Hdac siRNAs were employed to investigate effects on Kcnn1 mRNA levels. KCNN1 expression displayed side‐specific remodeling in AF/HF patients with upregulation in left and suppression in right atrium. In pigs, KCNN1 remodeling showed intermediate phenotypes. HDAC levels were differentially altered in humans and pigs, reflecting highly variable epigenetic regulation. Tachypacing recapitulated downregulation of Hdacs 1, 3, 4, 6, and 7 with a tendency towards reduced Kcnn1 levels in vitro, indicating that atrial high rates induce remodeling. Finally, Kcnn1 expression was decreased by knockdown of Hdacs 2, 3, 6, and 7 and enhanced by genetic Hdac9 inactivation, while anti‐ Hdac 1, 4, and 5 siRNAs did not affect Kcnn1 transcript levels. In conclusion, KCNN1 and HDAC expression is differentially remodeled in AF complicated by HF. Direct regulation of KCNN1 by HDACs in atrial myocytes provides a basis for mechanism‐based antiarrhythmic therapy. Abstract : Atrial KCNN1 channels are remodeled in patients and pigs with atrial fibrillation. KCNN1 remodeling is associated with changes in histone deacetylase (HDAC) expression: Inactivation of Hdac9 enhances Kcnn1, Knock‐down of Hdacs 2, 3, 6, and 7 suppresses Kcnn1. KCNN1 regulation by HDACs serves a basis for mechanism‐based antiarrhythmic therapy.